Organizational behavior in international strategic alliances and the relation to performance – a literature review and avenues for future research - Marius G. Gehrisch; Stefan Süß (Management Review Quarterly, 2022)
This paper presents a systematic literature review of the research on behavioral factors influencing the performance of international strategic alliances. After capturing the relevance of the research field, we observe the distribution of publications and derive quantitative metrics. Further, we focus on the terms related to alliance performance used in this research domain. Then, the results regarding the behavioral factors of influence on the individual, group-related and organizational level and their relation to alliance performance are stated. Our analysis ascertains that some factors are present on at least two behavioral levels and are understood differently on each level, leading to a certain multidimensionality. Therefore, we develop a categorization that cross all behavioral levels based on four broad categories: relational factors, learning and knowledge, conflict, and other (unrelated) factors. Based on this analysis, we identify avenues for future research. Beside methodological needs for research, gaps concerning the multidimensionality we recognized and various influencing factors are identified, as ambiguous results are apparent or other factors have been scarcely analyzed so far.
Keywords: D23; F53; M16; 650; Organizational behavior; International strategic alliances; Performance; Literature review